Association of child maltreatment and school bullying among Chinese adolescents: the mediating role of peer relationships - Linlin Xie; Pan Wen; Jiajun Zhou; Xiujuan Li; Jiayu Huang; Liping Li (BMC, 2024)
Abstract Background School bullying, a serious problem for the physical and mental health of adolescents, is presently a significant issue in China. It is essential to recognize and comprehend potential risk factors and establish efficient preventive strategies. The purpose of this study was to examine the association between childhood maltreatment and school bullying in adolescents and to assess the mediating role of peer relationships. Methods Between March and April 2024, a cross-sectional survey was conducted among 2119 adolescents aged between 12 and 18 years in Guangdong Province, China. Self-report questionnaires were employed to collect data on childhood maltreatment, school bullying, and peer relationships. Subgroup analyses and mediating effects modeling were employed to analyze the data. Results The results indicated that adolescents who had experienced maltreatment were more at risk of bullying victimization (OR: 2.92, 95% CI: 2.34-3.64, P < 0.001), bullying perpetration (OR: 2.84, 95% CI: 1.99-4.05, P < 0.001), and bully-victimization (OR: 2.93, 95% CI: 1.95-4.41, P < 0.001), compared to adolescents who have not. Sexual abuse showed the most significant connection with all forms of bullying. The mediating effect of peer relationships was found to mediate the association between child maltreatment and bullying behaviour. The results indicated that worse peer relationships may exacerbate the adverse effects of maltreatment experiences and increase the risk of adolescents becoming bullies, either perpetrators or victims of bullying. Conclusions Child maltreatment has been identified as one of the most significant influences on bullying behaviour in adolescents. The quality of peer relationships has been demonstrated to play an important role in preventing and reducing the occurrence of bullying. The results underscore the crucial role of early intervention in cases of child maltreatment and the fostering of positive peer relationships in schools.